Os Cuboideum Secundarium: A Rare Accessory Ossicle in the Foot - Arne Vermeulen; Nirav Gupta; Seema Döring (Journal of the Belgian Society of Radiology, 2023)
Teaching Point: Knowledge of the accessory ossicles in the foot and the possible disorders of these ossicles are important to prevent misdiagnosis and mistreatment.